Verdi's La Traviata - Piave, Francesco Maria, 1810-1876.; Fisher, Burton D.; Piave, Francesco Maria, 1810-1876.; Piave, Francesco Maria, 1810-1876.; Verdi, Giuseppe, 1813-1901.; Dumas, Alexandre, 1824-1895. (Coral Gables, Fla. : Opera Journeys Pub., 2001)
A newly translated Libretto featuring foreign language/English side-by-side, and music examples interspersed throughout the text.
Libretto by Francesco Maria Piave.
eBooks on EBSCOhost
Keywords: Verdi, Giuseppe, -- 1813-1901.; Traviata (Verdi, Giuseppe); Operas -- Librettos; Opéras -- Livrets; MUSIC -- Genres & Styles -- Opera; Operas -- Librettos